Teaching Training in Art and Craft: Drawing as a Performative Act - Samira Jamouchi (European Teacher Education Network, 2017)
Drawing is the most usual activity in Norwegian kindergartens. But it seems that the process during the act of drawing is not fruitfully valued. I have used a performative drawing form to meet the new National Curriculum of Kindergarten Teacher Education, but mostly in order to disclose the importance of a creative process while drawing. This project is empirically based, using photographs, video records and written feedback from the students to unveil their experience of performative drawing. The results show how students expanded their understanding of what a drawings session can be, and that this encourage them to new creative praxis in their kindergarten.